Analisis Cemaran Logam Berat Kadmium dan Timbal pada Liptint Merek Peiyen Unicorn yang Dijual di Toko Online Menggunakan Spektrofotometri Serapan Atom: Analysis of Heavy Metal Contaminants Cadmium and Lead in Peiyen Unicorn Brand Liptint Sold Online Using Atomic Absorption Spectrophotometry - Nurul Fithri Fauziyah; Leli Nurlaeli; Riasa Barata Nian (UIMA Press, 2023)
Along with the development of cosmetics, one of them is lip coloring in recent years, namely liptint. Lip color manufacturers favor the use of synthetic colors that contain harmful heavy metals because they are more affordable, stronger, more consistent, and more stable. However, heavy metals can have a negative effect on health such as hives, asthma, and even cancer. This study aims to determine how much heavy metal cadmium and lead are contamined in Peiyen Unicorn lip tint which is sold in online stores using atomic absorption spectrophotometry research methods. The results of this study were cadmium heavy metal contamination in Peiyen Unicorn liptint number 1 shade red and shade cherry red number 2 respectively ie 0.032 mg/kg and 0.025 mg/kg and results of lead heavy metal contamination in Peiyen Unicorn liptint sample number 1 shade red and number 2 shade cherry red respectively 0.004 mg/kg and 0.002 mg/kg. The test results for the cadmium heavy metal content in the two lipsticks still met the requirements, namely not more than 5 mg/kg according to the regulations of the Food and Drug Monitoring Agency. The results of the lead heavy metal test for the two lipsticks still met the requirements, namely not more than 20 mg/kg according to the regulations of the Food and Drug Administration. Based on the results of data analysis using ANOVA, it can be concluded that there was no difference in the levels of the heavy metals cadmium and lead between the Peiyen Unicorn lipstick samples number 1 shade red and shade number 2 cherry red.